Pengaruh Metode Outdoor Study Berbantuan Media Sticky Notes terhadap Kemampuan Menulis Karangan Deskripsi Siswa Kelas IV Sekolah Dasar - Mauliddiniar, Tiara Shaqinah; Azmy, Bahauddin (Lembaga Yasin AlSys, 2025)
The purpose of this study was to determine the effect of the outdoor study method assisted by sticky notes media on the ability to write descriptive essays of grade IV students of SDN Bulak Banteng 1/263 Surabaya. This study is a quantitative experimental study. The research design used is Posttest-Only Control Design. The posttest was used to determine the results of class 4D which was given treatment and class 4C which was not given treatment. This study took place at SDN Bulak Banteng 1/263 Surabaya. The subjects in this study were grade 4 students, especially 4C and 4D in the 2024/2025 academic year with 48 students. The data collection technique was a test and the instrument used was a posttest. This is evidenced by the value of the T-test results which show the t count posttest of the control class and the experimental class of 4.630 and t table 1.697 so that 4.630> 1.697 and a significance of 0.000 <0.05. Therefore, it can be interpreted that the hypothesis is accepted based on the assumptions of the previous hypothesis.